2017
DOI: 10.1177/1087054717727350
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility, Effectiveness, and Process of Change of Mindfulness-Based Cognitive Therapy for Adults With ADHD: A Mixed-Method Pilot Study

Abstract: The adapted MBCT program seemed to be feasible for adults with ADHD and preliminary evidence for the effectiveness is shown. An adequately powered Randomized Controlled Trial (RCT) is needed to further examine the effectiveness of MBCT for ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…Instead, participants report that they found the silent day facilitating, because it helped them to deepen their meditation practice and gain more insight in their behavioral patterns. This finding is in line with the study of Janssen et al (Janssen 2017), that showed that a silent day was found helpful by people with ADHD as well.…”
Section: Main Findingssupporting
confidence: 92%
“…Instead, participants report that they found the silent day facilitating, because it helped them to deepen their meditation practice and gain more insight in their behavioral patterns. This finding is in line with the study of Janssen et al (Janssen 2017), that showed that a silent day was found helpful by people with ADHD as well.…”
Section: Main Findingssupporting
confidence: 92%
“…The finding that MBCT is especially cost-effective in patients who adhered to the treatment, implies that it is important to search for effective ways to increase the adherence, for instance by sending reminders for training sessions and actively contacting participants in case of no shows. A recent pilot study gave insight in perceived facilitators and barriers during MBCT which can, in some cases, be taken into account, such as offering a proper amount of directiveness by the teacher and stimulating helpful coping strategies (Janssen et al 2017).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Conflict of Interest The research team declares it had no part in developing the original MBCT program. AS, LJ, and SH made small modifications to this program as described in our pilot study (Janssen et al 2017). The team does not gain income from the sale of books on MBCT, nor does it gain income from giving lectures or workshops about it.…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%
“…Notably, one recent study (Janssen, de Vries, Hepark, & Speckens, 2017) used mixed quantitative-qualitative methodology to assess feasibility and impact of an adapted mindfulness-based cognitive therapy (MBCT) program for adult ADHD patients. Qualitative interviews explored the barriers and facilitators of the training, as well as the process of change.…”
Section: Adverse Events From Mbi Treatment Studies In Adhd Samplesmentioning
confidence: 99%
“…Reasons ranged from universal barriers, such as a family emergency or illness (Zylowska et al, 2008), to experiences of "too much restlessness" and "exacerbation of depression" (Hepark et al, 2015). "Unmet expectations" was a reason for dropping out in an adult treatment study (Janssen et al, 2017), and one adolescent dropped out for "too severe externalizing and behavioral problems to participate in a group setting in another study" (van der Oord, Bogels, & Peijnenburg, 2012). In Janssen and colleagues (2017), overall noncompleters were significantly older and reported higher levels of executive and general dysfunction, as well as poorer physical and mental health status.…”
Section: Adverse Events From Mbi Treatment Studies In Adhd Samplesmentioning
confidence: 99%